2014
DOI: 10.1108/s1058-749720140000021002
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Non-Economic Factors: An Analysis of Corporate Tax Compliance

Abstract: Purpose À This chapter applies an "integrative" model to examine the impact and interaction of economic and moral/social factors in the corporate tax compliance context. More specifically, it examines whether social norms moderate the effect of economic factors in this context.Design/methodology À Fifty-five MBA students assumed corporate CFO roles and analyzed a proposed aggressive corporate tax shelter transaction ("tax shelter"). Participants indicated whether they would recommend the tax shelter and answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Within the scope of corporate tax compliance, Downs & Stetson (2014) has three indications that are more applicable to economic and moral/social norms approaches. The first indication is that corporate taxpayers will comply with a tax regulation if the positive expected value is material.…”
Section: Tax Compliance Theorymentioning
confidence: 99%
“…Within the scope of corporate tax compliance, Downs & Stetson (2014) has three indications that are more applicable to economic and moral/social norms approaches. The first indication is that corporate taxpayers will comply with a tax regulation if the positive expected value is material.…”
Section: Tax Compliance Theorymentioning
confidence: 99%
“…The idea of a co-operative model offers the administration (governance) greater benefits with limited cost, which refers to the principle of efficient tax collecting (Slemrod, 1990). Modern tax compliance strategies focus more intensively on the social/ moral components of taxation, whereas nowadays, scientific findings often express doubts about the traditional view that tax avoidance and evasion can only be prevented through strict controls or investigations and severe penalties (Downs & Stetson, 2014).…”
Section: Croatian and Comparative Public Administrationmentioning
confidence: 99%
“…In the same vein, Wenzel (2004) indicated that social factors may significantly affect and meet the requirements of the deterrence procedures. Downs and Stetson (2014) indicated that social factors can have moderating effects on economic factors.…”
Section: Patriotismmentioning
confidence: 99%